SIMULATION TECHNOLOGY OF SUGAR BEET - Volokha, Mykola; Boldyrieva, Larisa (Proceedings of National Aviation University (archive), 2014)
The Article highlights specific features of process simulation and technical facilities related to sugar beetproduction. It reviews the literature sources and specifies distinctive properties of the created models . Basing upon theanalysis conducted the main principles of process simulation of sugar beet growing and cropping are proposed.